The Role of the Constitutional Council of the Republic of Kazakhstan on Human Rights - Nastaevich, A.M.; Saniyazdanovich, M.K. (Published by Canadian Center of Science and Education, 2015)
Solving the problem of the human rights is not only referred to enlarging of range of human being and citizen rights and freedoms, but also set in the Constitution of the Kazakhstan, or strengthening their guarantees. In fact the problem concerns considerable renovation of the whole concept of human being, citizen rights, duties and the practice of their constitutional realization. It is extremely important in the course of such process to take into account both intergovernmental and international aspects of the problem stipulated by the character of the researched problem.
Keywords: kinds and functions of the constitutional control; protection of the rights of citizens; the decision and the decision of the constitutional council of Republic Kazakhstan